Penerapan Metode Complex Proportional Assesment (COPRAS) dalam Pemilihan Dekan Fakultas Teknik - Sandya, Radzfin Turfa; Laluma, Riffa Haviani (Fakultas Sains dan Teknologi UIN Imam Bonjol Padang, 2024)
In the selection of the dean of the Faculty of Engineering, a multitude of factors are involved, encompassing academic experience, leadership track record, functional positions, publications, and recent educational history. Currently, the method of choosing the dean of the Faculty of Engineering at Sangga Buana YPKP University still involves a direct selection process by the foundation, with each academic program presenting a single candidate. This selection process is discussed within the internal Faculty of Engineering meeting and requires approval from the Faculty of Engineering senate. The purpose of this research is to expedite and simplify the process of selecting the dean of the Faculty of Engineering at Sangga Buana YPKP University. There are various methods that can be employed in making decisions of this nature, but in this study, the researcher applies the Complex Proportional Assessment (COPRAS) method. To obtain the necessary data for the application usage phase, the researcher conducted a series of interviews with two lecturers from the Faculty of Engineering at Sangga Buana YPKP University. Through calculations performed using the COPRAS method, the best results derived from the data used in this method were identified. Therefore, this system is deemed suitable and worthy of utilization.